PENGARUH PRESENTASE ALKALISASI NaOH TERHADAP KEKUATAN TARIK MATERIAL KOMPOSIT SERAT DAUN NANAS POLYESTER DENGAN METODE VACUUM INFUSION - Mohamad Irkham Mamungkas; Nur Subeki; Arief Andrian N. (ROTOR, 2019)
Pineapple leaf fiber is currently widely used in furniture and handicraft industries (UKM) because besides being easily available, inexpensive, does not endanger health, can reduce environmental pollution so that later on as a composite reinforcing fiber can overcome environmental problems. From the considerations above, this study aims to determine the effect of the alkalization treatment (NaOH) on the tensile strength test of pineapple leaf fibers by vacuum infusion method and to determine the type of fracture of pineapple leaf fiber composites after tensile testing. Before it is made into a composite of pineapple leaves, it is soaked for 2 hours. Manufacture of composite materials based on ASTM D683-03 standard. From the composite tensile test results obtained the highest average tensile strength in specimens treated with NaOH 6% which is 112 MPa. While the lowest at 0% NaOH treatment is 68 MPa. Composites treated with NaOH have higher agility than those not treated with NaOH. The highest agility is found in composites with the highest NaOH treatment.